(untitled) (Web of Teachers: Inderscience Research, 2025)
Dialects of Turkish are dialects spoken in different regions with distinct characteristics. These dialects have different pronunciation, vocabulary and grammatical features from the main language of the Turkish language, each reflecting the cultural and historical identity of their territory. Through dialects, information can also be obtained about the social, cultural and historical States of the region.